2021
DOI: 10.1002/mar.21478
|View full text |Cite
|
Sign up to set email alerts
|

Methodological structure for future consumer neuroscience research

Abstract: Consumer neuroscience-as a valuable complement to traditional, largely behavioral, research methods-is attracting increasing interest from researchers of marketing and consumer behavior. Although this field has made very important contributions, most consumer neuroscience studies to date have mainly focused on individuals' brain responses to simple marketing stimuli in solitary, lab-based, albeit well-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 154 publications
(242 reference statements)
0
29
0
2
Order By: Relevance
“…Even more, when it comes to the factors that may elicit nearly automatic visceral, “gut,” or emotional reactions, individuals may not be able to actually articulate how or what they were feeling, or why they like or dislike certain media or products (Schwarz & Clore, 2003). There is a need for more “objective” measures of direct and implicit processes of perception and decision‐making while viewing advertisements (Ariely & Berns, 2010; Griffin & Hauser, 1993; He et al, 2021; Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even more, when it comes to the factors that may elicit nearly automatic visceral, “gut,” or emotional reactions, individuals may not be able to actually articulate how or what they were feeling, or why they like or dislike certain media or products (Schwarz & Clore, 2003). There is a need for more “objective” measures of direct and implicit processes of perception and decision‐making while viewing advertisements (Ariely & Berns, 2010; Griffin & Hauser, 1993; He et al, 2021; Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Venkatraman et al (2015), in a study with functional magnetic resonance imaging (fMRI), demonstrated that activation in the ventral striatum, a component of the mesolimbic system typically associated with reward processing and motivation (Tremblay et al, 2009), explained the most variance in advertising preference beyond traditional measures (see also Brown et al, 2011 for studies across several media types relating similar reward areas to pleasurable or positive assessment). In electroencephalography (EEG), high‐frequency EEG components of participants while watching movie trailers have been correlated with both individual preference (beta activity) and population preference (gamma activity) of the upcoming movies (Boksem & Smidts, 2015; see He et al, 2021 for review).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations